2018
DOI: 10.1111/jopr.12760
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid Axial Wall Height Effect on CAD/CAM Crown Fracture Mode on Preparations Containing Advanced Total Occlusal Convergence

Abstract: Further evidence is provided that CAD/CAM adhesive techniques may compensate for less than ideal preparation features. Under the conditions of this study, bicuspid preparations with a 20° TOC restored with adhesively luted, CAD/CAM e.max CAD crowns require at least 2 mm of axial wall height, but further planned fatigue studies are necessary before definitive recommendations can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Some authors [17] also found no significant differences between endocrowns and conventional crowns. Although studies using flat preparations [14, 15] have shown basically adhesive failures that presented lower values, in this study only 1 specimen showed adhesive failure (CP0 group), which was repairable and explainable because of enamel's absence. In all other tests samples' failures were irreparable presenting similar result to another study [26] and contrasting to other literature results.…”
Section: Discussioncontrasting
confidence: 59%
“…Some authors [17] also found no significant differences between endocrowns and conventional crowns. Although studies using flat preparations [14, 15] have shown basically adhesive failures that presented lower values, in this study only 1 specimen showed adhesive failure (CP0 group), which was repairable and explainable because of enamel's absence. In all other tests samples' failures were irreparable presenting similar result to another study [26] and contrasting to other literature results.…”
Section: Discussioncontrasting
confidence: 59%
“…A strong bonding between crown material and tooth structure can be achieved with adhesive cementation due to the presence of the etchable glass component in glass‐ceramics 22,23 . This advantage compensates for the excessive tooth tapering often produced by dental students or inexperienced dentists and for teeth with short clinical crown height or preparations lacking retention form 24,25 .…”
mentioning
confidence: 99%
“…However, the critical regions of possible fracture origin are the same in all evaluated groups. Finally, the complete simplification of the specimen using a dentin substitute without periodontal ligament, pulp chamber, root canals or anatomic roots is also possible (10). This is the most easily attainable specimen type due to its various simplifications, keeping only the crown anatomy as a similar geometry to that found in the oral environment.…”
Section: Discussionmentioning
confidence: 99%